RETRACTED: RBFOX3 Promotes Gastric Cancer Growth and Progression by Activating HTERT Signaling - Luo, Chen; Zhu, Xiaojian; Luo, Qilin; Bu, Fanqin; Huang, Chao; Zhu, Jingfeng; Zhao, Jiefeng; Zhang, Wenjun; Lin, Kang; Hu, Cegui; Zong, Zeng; Luo, Hongliang; et al. (Frontiers in Oncology, 2020)
Tumor invasion, metastasis, and recrudescence remain a considerable challenge in the treatment of gastric cancer (GC). Herein we first identified that RNA binding protein fox-1 homolog 3 (RBFOX3) was markedly overexpressed in GC tissues and negatively linked to the survival rate of GC patients. RBFOX3 promoted cell division and cell cycle progression in vitro and in vivo. Furthermore, RBFOX3 increased the cell invasion and migration ability. The suppression of GC cell multiplication and invasion, caused by silencing of RBFOX3, was rescued by HTERT overexpression. Additionally, RBFOX3 augmented the resistance of GC cells to 5-fluorouracil by repressing RBFOX3. Mechanistically, the exogenous up-regulation of RBFOX3 triggered promoter activity and HTERT expression, thereby enhancing the division and the development of GC cells. Further co-immunoprecipitation tests revealed that RBFOX3 bound to AP-2β to modulate HTERT expression. In conclusion, our study indicates that a high expression of RBFOX3 promotes GC progression and development and predicts worse prognosis. Collectively, these results indicate that the RBFOX3/AP-2β/HTERT signaling pathway can be therapeutically targeted to prevent and treat GC recurrence and metastasis.